Analysis of the housing insurance contract and the exclusion of coverage for construction defects in the light of the Consumer Protection Code (Revista do Tribunal Regional Federal da 3ª Região, 2020)
The purpose of this article is to analyze the housing insurance agreement, which is considered to be a typical subscription agreement, and the interpretation given by court precedents of clauses that exclude coverage for building defects signed in the scope of Financial Housing System. Based on the principles of objective good faith, the social function of agreements and the protective rules of the Consumer Protection Code.
Keywords: subscription agreement; housing insurance agreemente; clauses that exclude coverage; building defects; objective good faith; social function of the agreement; consumer protection code